O conceito de Patrimônio Cultural Digital na Ciência da Informação e os quadros ultramodernos da memória social - Grimaldi, Stphanie Sá Leitão (2020)
The frames of social memory that are constituted by digital cultural heritage and taken by digital information indicate that socio-cultural changes are imposed, in ultramodernity, also by cyberculture, but also by a complexity of traces left by other forms of non-digital technology. With this proposition the main objective is to analyze how the implementation and use of the concept of Digital Cultural Heritage in Information Science affects the frames of social memory and the identities that are observed in the socio-cultural environments of ultramodernity. It establishes, as a hypothesis, that the (re) appropriations that occur with the concept of Cultural Heritage directly affect the changes in the frames of social memory and identities in ultra-modern socio-cultural environments. The specific objectives are: To identify appropriations and reformulations of the concept of Cultural Heritage and Digital Cultural Heritage in the production of Information Science in Brazil; compare the conceptual perspectives on Cultural Heritage in its analog and digital facet; to identify policies and initiatives for the preservation of Cultural Heritage in the digital sphere; relate the concept of Cultural Heritage to current conservation initiatives and policies; map the nature of the concept of digital information; describe the concept of culture in the digital socio-cultural context that permeates ultramodernity; discuss the frameworks of social memory and contemporary socio-cultural identities imposed by the digital environment. A qualitative and quantitative research is used. It uses a bibliographic research as to the concept of digital information and digital cultural heritage, in addition to a descriptive research, with bibliographic and documentary research to support the concepts related to the theme. With the questionnaire instrument, information about social networks and their configuration in social memory is collected, supported by the theoretical framework of this research. As a result, it was noticed that social networks contribute to an important factor of large-scale exposure of digital objects categorized as digital cultural heritage, inclusive. Its way of preservation is through use, exposure, dissemination, dissemination and, when not deleted, memorial records through individual views, which will constitute a social memory. We understand that in ultramodernity, digital assets are an integral part of the changes that occurred both in the memorial frames and in the identities of the subjects. In addition, we understand that information is found in digital media, but it is, above all, information.